Pengaruh Model Pembelajaran Field Trips terhadap Hasil Belajar pada Materi Ilmu Sosial Siswa Kelas IV SDN 104212 Marindal II - Masliani, Masliani; Malinda, Leni; Harahap, Syarifah Ainun (Medan Resource Center, 2024)
This study investigated the effect of the Think Pair and Share cooperative learning model on the science learning outcomes of fourth-grade students at Marindal II Elementary School, North Sumatra. The research, using an experimental method, involved 53 students divided into two groups: the experimental group applied the Think Pair and Share model, while the control group used conventional methods. Data were collected through pretest and posttest scores, as well as non-test observations, including teacher performance and student activity. Results showed that the experimental group achieved higher learning outcomes, with an average score of 84.40, compared to 69.46 in the control group. The study concluded that the Think Pair and Share model significantly improved student science learning outcomes. It is recommended that this model be adopted by teachers to enhance student engagement and performance.